Cover. (September 2017) - Kofod, Louise; Lindhard, Anette; Bzorek, Michael; Eriksen, Jens Ole; Larsen, Lise Grupe; Hviid, Thomas Vauvert F.
Abstract : Front cover : The cover image, by Louise Kofod et al., is based on the Original Article Endometrial immune markers are potential predictors of normal fertility and pregnancy after in vitro fertilization, DOI:10.1111/aji.12684 .